High rates of SARS-CoV-2 infection in funeral home workers in Ecuador: Is it an occupational risk for COVID-19? - Ortiz-Prado, Esteban; Vásconez, Jorge Eduardo; Vallejo-Janeta, Alexander Paolo; Morales-Jadán, Diana; Henriquez-Trujillo, Aquiles R.; Rivera-Olivero, Ismar A.; Andrade, Felipe; Lozada, Tannya; Garcia-Bereguiain, Miguel Angel; , UDLA COVID-19 Team (Frontiers in Public Health, 2022)
Aim. The COVID-19 outbreak has already caused more than 2 million deaths, overwhelming health systems worldwide. The unusual demand of funeral home services could make these workers a potential risk group for occupational exposure to SARS-CoV-2 associated to corpses management from COVID-19 patients. Methodology. A cross-sectional study to describe the infection rate of SARS-CoV-2 in funeral homes staff by testing them by RT-qPCR was carried out in Quito, Ecuador. A total of 232 funeral homes workers, representing more that 40% of funeral homes personnel in Quito, were included on the study, done in june 2020, right after the population lockdown was lifted in Ecuador. Results. 48 individuals tested positive for SARS-CoV-2, yielding an infection rate of 20.7%. The SARS-CoV-2 infection rate was 18.1% and 20.0% among personnel managing corpses or not, respectively. Among the SARS-CoV-2 positive patients, 81.3% reported no symptoms related to COVID-19, and 3 individuals had high viral loads over 108 copies/mL. Conclusions. The high SARS-CoV-2 infection rate in funeral homes staff suggest a potential occupational risk for COVID-19 but not related to corpses management. Public health guidelines not only for safe corpses management from COVID-19 victims but also for safe funeral services should be reinforced.